Rethinking import-substituting industrialization: Development strategies and institutions in Taiwan and China - Tianbiao Zhu (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2006)
Conventional explanations of Taiwan and China's economic success point to the shift from an import-substituting industrialization (ISI) strategy to an export-oriented industrialization (EOI) strategy. This paper argues that the development strategies in Taiwan and China have always been a combination of ISI and EOI strategies during their entire miracle-creating period; far from the shift from ISI to EOI strategies, export promotion was used in both cases to sustain ISI, which has always been the central focus of development. Behind this strategy there is a set of institutions in both Taiwan and China, which has played a key role in supporting ISI, in particular, the government, the bank sector, public enterprises, and their relationship.
Keywords: N15; N45; O20; O53; 330; import-substituting industrialization; export-oriented industrialization; development strategies; institutions; Industrialisierung; Importsubstitution; Exportdiversifizierung; Entwicklungsstrategie; Taiwan; China